2010
DOI: 10.1021/jp907696t
|View full text |Cite
|
Sign up to set email alerts
|

Diffusiophoresis of a Charge-Regulated Spherical Particle Normal to Two Parallel Disks

Abstract: The diffusiophoresis of a charge-regulated spherical particle normal to two parallel disks as a response to an applied uniform electrolyte concentration gradient is modeled theoretically. The fixed charge on the particle surface comes from the dissociation/association reactions of the functional groups, yielding a charge-regulated surface, which simulates biological cells. Numerical simulations are conducted to examine the behavior of a particle under various conditions: the parameters considered in the simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 31 publications
1
46
0
Order By: Relevance
“…As ka p increases, the type I (II) DLP increases (decreases), leading to the increase (decrease) in the induced electrophoresis driven by E IÀDLP (E IIÀDLP ). [48] The two competing opposite electrophoretic effects by E IÀDLP and E IIÀDLP lead to the decrease in the particle velocity as ka p increases. When ka p > (ka p ) c , the induced electrophoresis driven by E IÀDLP becomes dominant, leading to the particle migrating toward higher salt concentration, and the particle velocity increases as ka p further increases.…”
Section: Effect Of the Ratio Of Particle Size To Edl Thickness Ka Pmentioning
confidence: 99%
See 1 more Smart Citation
“…As ka p increases, the type I (II) DLP increases (decreases), leading to the increase (decrease) in the induced electrophoresis driven by E IÀDLP (E IIÀDLP ). [48] The two competing opposite electrophoretic effects by E IÀDLP and E IIÀDLP lead to the decrease in the particle velocity as ka p increases. When ka p > (ka p ) c , the induced electrophoresis driven by E IÀDLP becomes dominant, leading to the particle migrating toward higher salt concentration, and the particle velocity increases as ka p further increases.…”
Section: Effect Of the Ratio Of Particle Size To Edl Thickness Ka Pmentioning
confidence: 99%
“…thick EDL and small gap between the particle surface and nanopore wall), the EDL surrounding the charged nanoparticle is compressed by the nanopore wall, and the type I DLP mainly arises from the EDL compression by the boundary. [34,37,38,48] If the EDL compression by the nanopore wall is insignificant, as the ratio a/a p increases, the degree of DLP decreases, leading to the decrease in the induced electrophoresis arising from the DLP-induced electric fields.…”
Section: Effect Of the Particle Surface Charge Density S Pmentioning
confidence: 99%
“…The first one comes from a deformed EDL, known as chemiphoresis or double-layer polarization (DLP). Two types of DLP need be considered: type I (II) DLP occurs inside (outside) the EDL, yielding a local electric field driving the particle toward the high-(low-) concentration side [17][18][19][20]. The second one arises from the difference in the ionic diffusivities, known as electrophoresis effect [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Dukhin and Deryagin (1974) initiated the analysis of diffusiophoresis and proposed that it plays a significant role in the deposition of rubber latex films on a salt-coated surface. If the liquid phase is an electrolyte solution, then the mechanisms involved in diffusiophoresis include double-layer polarization (DLP) (Hsu et al, 2009b), electrophoresis (Hsu et al, 2007b;Pawar et al, 1993), solvent flows (Chen and Keh, 2005;Hsu et al, 2010c;Keh and Ma, 2005), and the interaction between the coins outside the double layer and the particle (Hsu et al, 2010a). Because these mechanisms are not independent of each other, the phenomenon under consideration is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, depending upon the geometry considered, the presence of a boundary is capable of accelerating, decelerating, and even reversing the direction of diffusiophoresis. The geometries considered in previous studies include, for example, a charged particle moving normal to a plane (Keh and Jan, 1996;Lou and Lee, 2008), parallel to two parallel planes (Chen and Keh, 2005), perpendicular to two parallel planes (Hsu et al, 2010c), in a spherical cavity (Hsu et al, 2009b;Zhang et al, 2009), and along the axis of a cylindrical pore (Hsu et al, 2010a). Hsu et al (2010a) found that the diffusiophoretic behavior of a sphere in the cylindrical pore can be quite different from that in other types of boundary.…”
Section: Introductionmentioning
confidence: 99%